YAKUZA: ORGANISASI, VARIAN, DAN CARA BERBISNIS - , MOHAMAD ARRAHMAN; , Drs. Deddy H. Oekon, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yakuza is the largest criminal organization in Japan. Yakuza can be divided into two based on its term